Pengaruh Kecerdasan Emosional terhadap Penyesuaian Diri Mahasiswa Thailand - Ahmad, Muhammad Yusuf; Tambak, Syahraini; Hasanah, Uswatun (UIR Press, 2018)
Individual self-adjustment is needed for survival, because humans are social beings who cannot live without others. Self-adjustment is very necessary if someone moves from one place to another. Self-adjustment greatly encourages them to improve their standard of living, not only in the fields of Education but also Economics, Social, Culture, Religion and so on. Of course, in this case, it is inseparable from problems and difficulties in communication, Thai students who study at the faculty of Islamic religion in islamic university of Riau found difficulties to adjust, because of lacking of mastering Indonesian language, communicating, lacking mingling with Indonesians, tend to be quiet many times, and also often gather with fellow Thai students, then the problem formulation in this study iswhether there is an influence of intelligence Emotional towards Thai Student Adaptation. The purpose of this study was to find out the effect of Emotional Intelligence on Thai Student Adaptation. This study is a type of correlation research that aims to find out how much influence of emotional intelligence on the self-adjustment of Thai students. Sampling used is saturated sampling method which involve the entire population to be used as a research sample because the population was less than 100 people, namely 33 students.To collect data using questionnaires and documentation, data analysis techniques using simple linear regression analysis. Based on the results of data analysis in the ANOVA table, it can be concluded that the significant value is 0.926, which means that there is no significant influence between Emotional Intelligence and Thai Student Adaptation.